Pengembangan Media Computer Assisted Instruction (CAI) Untuk Perhitungan Volume Pekerjaan dan Analisis Biaya Bahan Pada Kompetensi Keahlian Teknik Konstruksi Batu Beton - Dhani Harda Setiaji (JTP - Jurnal Teknologi Pendidikan, 2016)
The Research and development aimed at generating Computer Assisted Instruction (CAI) media that can help the 11th grade students of Vocational High Schools (VHS) in the comprehension process of working volume calculation and materials cost analysis. The research is conducted at SMKN 4 Rorotan of Northern Jakarta. The development model used here is the combination between Dick and Carey and Hannafin and Peck model. The results of formative evaluation: experts, one to one, small group, dan field group indicate that, the product is classified as â€œgoodâ€. It can be concluded that the CAI media that has been developed to help students in the comprehension process can help teachers in teaching material.